Nociceptive pain in late-onset Pompe disease: prevalence, distribution, and clinical correlates - Stephan Wenninger; Marcela Arndt; Daniel H. Mendelsohn; Corinna Wirner-Piotrowski; Marko Mijic; Natalia Garcia-Angarita; Kristina Gutschmidt; Christoph Schmidt; Lisa Winkler; Dieter Gläser; Karl Christian Knop; Matthias Spranger; et al. (Journal of Neurology, 2026)
Abstract Background Nociceptive pain is often recognized as a relevant symptom in late-onset Pompe disease (LOPD), yet its prevalence, distribution, and underlying determinants remain insufficiently characterized. We aimed to systematically assess nociceptive pain in LOPD and to explore its relationship with muscle function, structural muscle alterations, and potential modifiers. Methods In this multicenter cross-sectional study, 42 patients with LOPD and 61 disease controls (IBM, FSHD, SMA3) were evaluated. Pain was assessed using validated questionnaires and pain drawings. Motor function tests, pressure pain thresholds, muscle ultrasound, laboratory parameters, and genetic polymorphisms (ACE, ACTN3) were obtained. Associations between pain and clinical, structural, and biological variables were analyzed. Results Chronic nociceptive musculoskeletal pain was highly prevalent, particularly in LOPD (83.3%) compared to disease controls ( p =0.005). However, pain reported on the assessment day was significantly lower in LOPD (30.9%, p